A Survey of Human Face Mites Demodex (Acari, Demodicidae) in Patients with Dermatological Symptoms in Baghdad, Iraq - Bedair, Basma H.; Salman, Suhaila D.; Abtan, Azhaar F. (Iraqi Journal of Science, 2021)
Demodex spp. mites are external obligate parasites; they are transmitted between hosts through direct contact, and may induce several dermatological symptoms when found in large numbers. However, these symptoms may be similar to other commonly known diseases; this often leads dermatologists to neglect the pathogenic role of these mites. Therefore, a better diagnosis is recommended in order to avoid mistreatment. The aim of this study was to investigate the correlation between Demodex mites and dermatological diseases. Infestation rates in patients suffering from acne, rosacea, folliculitis, and psoriasis were compared with asymptomatic patients, along with the mites’ relation to gender, age, personal hygiene, time of year, and residency. These mites were mainly found in patients with rosacea (66.67%) followed by acne (64.41%), while they were only observed in 48.15% of asymptomatic patients, 40.00% in folliculitis, and 0.00% in psoriasis. The statistical analysis showed a significant relationship between infestation and the previously mentioned dermatological diseases (P<0.01). The infestation rates increased significantly with age, reaching 83.33% in patients above 60 years old, and especially during cold months with higher humidity rates. These mites were also more predominantly found in urban areas (56.10%), followed by rural areas (48.45%). However, there was no significant relationship according to gender or personal hygiene.